Evaluation of spiral acquisition variants for functional imaging of human superior colliculus at 3T field strength. Issue 4 (24th July 2017) - Singh, Vimal; Pfeuffer, Josef; Zhao, Tiejun; Ress, David
Abstract : Purpose: High‐resolution functional magnetic resonance imaging of human subcortical brain structures is challenging because of their deep location in the cranium, and their comparatively weak blood oxygen level dependent responses to strong stimuli. Magnetic resonance imaging data for subcortical brain regions exhibit both low signal‐to‐noise ratio and low functional contrast‐to‐noise ratio. To overcome these challenges, this work evaluates the use of dual‐echo spiral variants that combine outward and inward trajectories. Specifically, in‐in, in‐out, and out‐out combinations are evaluated. For completeness, single‐echo spiral‐in and parallel‐receive‐accelerated echo‐planar‐imaging sequences are also evaluated. Methods: Sequence evaluation was based on comparison of functional contrast‐to‐noise ratio within retinotopically predefined regions of interest. Superior colliculus was chosen as sample subcortical brain region because it exhibits a strong visual response. All sequences were compared relative to a single‐echo spiral‐out trajectory to establish a within‐session reference. Results: In superior colliculus, the dual‐echo out‐out outperformed the reference trajectory by 55% in contrast‐to‐noise ratio, while all other trajectories had performance similar to the reference. The sequences were also compared in early visual cortex. Here, both dual‐echo spiral out‐out and in‐out outperformed the reference by ∼25%. Conclusion: Dual‐echo spiral variants offer improved contrast‐to‐noise ratio performance for high‐resolution imaging for both superior colliculus and cortex. Magn Reson Med 79:1931–1940, 2018. © 2017 International Society for Magnetic Resonance in Medicine.